Efektivitas Pskoedukasi Personal Safety Dalam Meningkatkan Kesadaran Siswi SMP Terhadap Bahaya Child Grooming - Mulfik Ahmad Hanif; Maharani Tyas Budi Hapsari (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2026)
Background: Cases of sexual violence against children, especially girls, are still rampant, one of which is in the form of child grooming. Their lack of understanding of the signs of grooming and self protection skills makes them more vulnerable to becoming victims. Objective: This study aims to examine whether personal safety psychoeducation is effective in increasing junior high school girls' awareness of the dangers of child grooming. Method: This study used an experimental method with a one-group pre-test post-test design, involving 8 female junior high school students at SMP X in Boyolali. Participants were obtained using purposive sampling. The research instrument was a child grooming scale compiled with reference to the aspects proposed by O'Connell. Data analysis used the Wilcoxon Signed Rank Test with the help of SPSS version 22 software. Result: The study showed that personal safety psychoeducation was effective in increasing the awareness of junior high school students at SMP X. This was evidenced by an increase in personal safety skills scores and an increase in students' awareness of the dangers of child grooming, with a significance value of 0.018 (p<0.05). Conclusion: Education on personal safety skills is important for adolescent girls to avoid the dangers of child grooming, which is a subtle and gradual form of abuse. By understanding these dangers and having good personal safety skills, the number of victims of child sexual abuse can be minimized.